(untitled) (Research, Society and Development, 2021)
Different calibers and compositions of suture threads are found in commerce. A correctly performed suture, respecting the suture’s mechanical properties, such as tensile strength and adequate gauge, generates a favorable environment for hemostasis and tissue repair. The aim of this study was to evaluate the tensile strength of the most commonly used suture threads in dentistry through bibliographic, experimental, descriptive, and quantitative research, with systematic data tabulation and analysis. The sample of this experiment consisted of 25 threads that were divided into five experimental groups, taking into consideration their composition and caliber. Quantitative evaluation of tensile strength and deformation of suture threads was performed using an EMIC universal press with INSTRON operating system. The cardinal variables, obtained by measuring strength and deformation, were evaluated by analytical statistics for comparison of groups. Among the results found, the Nylon 3.0 wire proved to be the most resistant among the specimens, with an average force of 29.08 N and average deformation of 40.58 mm. It was found that in relation to strength and deformation, Nylon yarns are more resistant to traction than Silk yarns. Regarding strength and gauge, the yarns with larger diameter showed higher tensile strength, especially Nylon yarns. Regarding deformation and gauge, there was no statistical difference when suture threads of the same material were compared.